Physico-chemical and bacteriological characterisation of surface water in Bamenda (North West Cameroon) - Alice Magha Mufur (SpringerOpen, 2021)
Abstract The Mezam River and its tributaries constitute a prominent water source for domestic use and vegetable irrigation in Bamenda Town (North West Cameroon). The river flows through the city and is thus vulnerable to impairment by substances from point and non-point sources. This current research aims to assess the degree of pollution of the Mezam River water to ascertain its suitability for various uses. A total of 24 water samples were collected from six segments of the Mezam River basin in the dry and rainy seasons during the years 2015 and 2016 in view of physico-chemical and bacteriological analyses. In situ measurement of physical parameters was taken in the field. The data were analysed by multivariate statistical techniques (principal component analysis and factor analysis). The results revealed that the river water is slightly acidic (pH = 5.45–6.47) and ion concentration is low (41.67–237.00 µS/cm). The water type is Ca-SO4 and Ca-Mg-(Cl + NO3) in the dry season and Ca-Mg-SO4 in the rainy season. High NO3 − values (50 mg/l) are recorded at Nkimefueh. The Mezam River water is heavily polluted with indicator bacteria (0–500 CFU/100 ml) whose concentrations steadily increase from the reference point (YB) through sampling points in the city centre, suggesting the influence of human-induced activities. The population is urged to adopt a responsible behaviour towards waste disposal and refrain from disposing waste in water courses in order to safeguard the aquatic environment and also protect the health of the population.